Cloning and erxpression if pullulanase agene from locally isolated bacillus - Md. Salleh, Madihah; Hassan, Osman; Md. Illias, Rosli; Shahab, Neelam (Faculty of Science, 2006)
A pullulanase-producing bacteria has been identified as Exiguobacterium sp. MAAC-1 using 16S rRNA gene sequence analysis. Exiguobacterium sp. MAAC-1 achieved optimum pullulanase production at 22 hours incubation at 37 oC in modified Peptone Yeast Extract (PYE) medium. The optimum temperature and pH of the crude enzyme were 60 oC and pH 9.0 respectively. Plackett-Burman design was applied in the screening process of 17 nutrients for pullulanase production and five nutrients were identified as significant and effective factors for the pullulanase production. The five significant factors are sago starch, NH4Cl, Na2HPO4, KCl and MgSO4. The five nutrients were selected for further optimization studies using Central Composite Design (CCD). Optimum pullulanase production was achieved using 3.86%w/v sago starch, 0.002% w/v NH4Cl, 0.05%w/v Na2HPO4, 0.015%w/v KCl and 0.025 %w/v MgSO4, with predicted pullulanase activity, 1.252 U/ml. The experimental pullulanase activity was achieved at 1.208 U/ml. About 9.6-fold increment of pullulanase production was achieved after medium optimization process. For the pullulanase gene isolation, 1177 bp of partial pullulanase gene was amplified and showed the highest homology of 60 % with pullulanase gene from Exiguobacterium sp. 255-1. The four conserved regions of amylolytic enzyme, conserved region I, II, III and IV, and a highly conserved region of pullulanase type I (motif YNWGYDP) were found in the partial pullulanase gene.